2018
DOI: 10.1017/s1744137417000637
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of in-court settlements: empirical evidence from a German trial court

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…We also show that the anticipation of case duration plays a role on the settlement decision. The previous literature has investigated how the field of laws (Gross and Syveryd (1991); Eisenberg and Lanvers (2009)), the characteristics of the judge (Berlemann and Christman (2016)) the characteristics of the case (Kaplan et al (2008)), or the value of the claims (Lederman (1999); Huang et al (2010)) impact the settlement decision. We prove here that the anticipated case duration also matters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also show that the anticipation of case duration plays a role on the settlement decision. The previous literature has investigated how the field of laws (Gross and Syveryd (1991); Eisenberg and Lanvers (2009)), the characteristics of the judge (Berlemann and Christman (2016)) the characteristics of the case (Kaplan et al (2008)), or the value of the claims (Lederman (1999); Huang et al (2010)) impact the settlement decision. We prove here that the anticipated case duration also matters.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other determinants of settlement have been investigated. Settlement rates can vary according to the field of law (Gross and Syveryd (1991); Eisenberg and Lanvers (2009)), the values of the claims (Lederman (1999)), legal representation (Huang (2008)) or the characteristics of the judges (Berlemann and Christman (2016)). Eisenberg and Farber (1997) show that lawsuits where the plaintiff is an individual have higher trial rates than those where the plaintiff is a corporation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study based on a unique dataset of 860 case records from a German trial court seems to support the finding that female judges might be more able to moderate and also be more empathetic regarding existing malfunctioning relationships between the two parties than their male counterparts. Specifically, Berlemann and Christmann (2019) found that female judges seem to exhibit higher settlement rates in long-term contractual relationships, whereas male judges perform better when the parties concur “by chance”: Tenancy cases typically originate from friction in the long-term relationship between the litigants, and female judges more often arrange settlements between the parties in such cases, whereas the relationships in tort law cases are typically somewhat coincidental. These gender-related differences in settlement probability and interpretation of the results merit our attention.…”
Section: Major Findingsmentioning
confidence: 99%
“…The parties to the dispute may avoid significant costs of the proceedings and save a considerable amount of time and effort that would be associated with hearing on the merits (Elkins-Elliott and Elliott 2004, Blake 2009, Bone 2017. For a taxpayer-funded judicial system, a settlement reduces the time and financial burden associated with the conduct of proceedings, the written preparation of the judgment and potential appellate proceedings (Berlemann and Christmann 2019). From the societal perspective, in-court settlement contributes to the creation of a culture of amicable settlement of disputes (Andrews 2008), to a positive tendency of leaving the responsibility for dispute resolution in the hands of the parties (Blake 2009) and to re-establishment and preservation of the legal peace (Rechberger 2016).…”
Section: Introductionmentioning
confidence: 99%